Multimedia in Science Teaching: from a repository to an Education community - Jorge Miguel Gonçalves da Mota (2017)
The present dissertation proposal originates from the project Multimedia in science teaching: five years of research and teaching in Portugal, which featured, on the one hand, the national research on multimedia in science teaching, and on the other, provided the community with a simple reference tool - a repository of open access scientific texts - that would allow reflecting on teaching practices in science, technology, engineering and mathematics (STEM) areas using information and communication technologies and improving them from a participatory science perspective. This work intends to continue this last section, analyzing the conditions of genesis and sustainable development of an online community on science teaching, capable of appropriating and generating scientific peer review and validation processes. A literature review on social learning systems, such as communities of practice and affinity spaces, was carried out, and a syncretic notion was adopted to lead an action-research process. Pertinent modifications were applied to the current platform, in a sense of implementing strategies able to attract and to sustain an interested public and progressively to create a community of peers. The science teacher's behavioral intention of participation in the platform was also the object of study under the Theory of Planned Behavior. The project is particularly relevant in the national context, considering the gap between academic production and pedagogical practice, but also internationally, and it is possible to anticipate comparative research lines with other realities.